2002
DOI: 10.1073/pnas.182433099
|View full text |Cite
|
Sign up to set email alerts
|

The expression of growth hormone-releasing hormone (GHRH) and splice variants of its receptor in human gastroenteropancreatic carcinomas

Abstract: Splice variants (SVs) of receptors for growth hormone-releasing hormone (GHRH) have been found in primary human prostate cancers and diverse human cancer cell lines. GHRH antagonists inhibit growth of various experimental human cancers, including pancreatic and colorectal, xenografted into nude mice or cultured in vitro, and their antiproliferative action could be mediated in part through SVs of GHRH receptors. In this study we examined the expression of mRNA for GHRH and for SVs of its receptors in tumors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
78
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 51 publications
3
78
0
7
Order By: Relevance
“…The indirect, endocrine mechanism operates through the suppression of the GH release from the pituitary, and the resulting inhibition of the hepatic production of IGF-I [8,9]. In addition, it was observed that GHRH antagonists can inhibit the proliferation of diverse cancer lines by direct action in vitro, under conditions in which the contribution of the hypothalamic GHRH/pituitary GH/hepatic IGF-I axis is clearly excluded [8,[13][14][15][16][17][18][19][20][21][22][23][24][25]. These studies led to the conclusion that the main mechanism responsible for tumor inhibition could be a direct effect of the antagonists on the tumor tissue [8,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indirect, endocrine mechanism operates through the suppression of the GH release from the pituitary, and the resulting inhibition of the hepatic production of IGF-I [8,9]. In addition, it was observed that GHRH antagonists can inhibit the proliferation of diverse cancer lines by direct action in vitro, under conditions in which the contribution of the hypothalamic GHRH/pituitary GH/hepatic IGF-I axis is clearly excluded [8,[13][14][15][16][17][18][19][20][21][22][23][24][25]. These studies led to the conclusion that the main mechanism responsible for tumor inhibition could be a direct effect of the antagonists on the tumor tissue [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the expression of mRNA for GHRH or its peptide product were detected in surgical specimens of human endometrial, ovarian, breast and prostatic cancers [27,31,32]. mRNAs encoding four splice variants (SV) of GHRH receptors and specific high affinity binding sites for GHRH and its antagonistic analogs have been identified in diverse cell lines and specimens of human cancers [19,20,24,25,28,29,31,[33][34][35][36]. These findings suggest that the direct antiproliferative action of GHRH antagonists could be exerted through the disruption of an autocrine/paracrine stimulatory loop formed by tumoral GHRH and its receptors on tumors [14,19,20,28,29,35,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone-releasing hormone antagonists suppress the in vivo growth of various experimental cancers such as prostatic (Zarandi et al, 2006;Stangelberger et al, 2007), mammary (Buchholz et al, 2007), ovarian (Chatzistamou et al, 2001), renal cell carcinomas , small cell lung carcinomas (Hohla et al, 2006), pancreatic and colorectal carcinomas (Szepeshazi et al, 2000;Busto et al, 2002), endometrial (Engel et al, 2005), osteogenic sarcomas (Braczkowski et al, 2002) as well as malignant glioblastomas (Jaeger et al, 2005).…”
mentioning
confidence: 99%
“…Our group demonstrated that GHRH antagonists can inhibit tumor growth through indirect and direct pathways (2)(3)(4)(5)(6)(7). The indirect mechanism is based on the suppression of the pituitary GH-hepatic insulin-like growth factor (IGF)-I axis.…”
mentioning
confidence: 99%